Evaluation of the efficacy of chemical, ultraviolet (UV) and combination treatments on reducing microbial loads in water prior to irrigation - Van Rooyen, Brandon Burger (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc Food Sc)--Stellenbosch University, 2018.